(untitled) (Revista Venezolana de Salud Pública, 2019)
Health professionals are subject to stressful situations almost daily, the current Venezuelan reality means that these situations are not limited only to the workplace but even to the daily life of all citizens; In this sense, the successful resolution of these situations will depend on the subject’s own resilience, which will help reduce stress, improve physical and mental well-being and therefore the quality of service provided. Distribute the professionals according to social-labor variables; Determine the levels of resilience. A quantitative, correlational, non-experimental research was carried out. The population was constituted by the health personnel that worked in the PICU and the sample by 33 workers who met the inclusion criteria: more than 6 months working in the PICU. The average age was 38.6 years. More than 80% was female. The highest proportion was married (45.5%) and was from the nursing area (60.6%). More than 90% had at least more than 2 years of seniority. 45.5% presented average levels of resilience